O envolvimento de meninas e mulheres jovens em atos infracionais - Aranzedo, Alexandre Cardoso (2012)
Great part of Brazilian society has been concerned with the increase of violence and crime rates. Within this context, the academic interest is drawn to studies related to the issue of juvenile offenders, who are erroneously considered directly involved in the matter of public insecurity. In Brazil and in other countries, rises the involvement of women of all ages in criminal activities, especially in drug trafficking. On account of its social and scientific relevance, this study aims to analyze which processes contribute to the involvement of girls and young women in criminal activities. Aged between thirteen and nineteen, twenty female adolescents and young women were subjects of this research. They were either under the social-educational measure of assisted freedom or apprehended at The Female Internment Unit. Interviews were conducted about some aspects of their lives, such as trajectory, involvement in criminal activities, family and love relationships, crimes committed, experience of a social-educational measure and future prospects. In addiction, was applied an inductive instrument in order to investigate some aspects related to the subjects´ life trajectory: my life, to be a woman/to be a girl, to be a man/to be a boy, emotional relationship, family, crime, violence, drug trafficking, death and social-educational measures. The Social Representation Theory was chosen as theoretical approach for its penetration in the field of social and human sciences. Findings were discussed in three articles, namely: “Trajectories of girls in conflict with the law”, “Girls in conflict with the law and drug trafficking” and “Girls: conflict with the law and representations of social-educational measures”. Main data demonstrates that the majority of adolescents had connections with drug trafficking. In the analysis of their trajectories, were verified, within the family context, some factors that have contributed to their vulnerability, such as: presence of family conflicts, personal knowledge of criminals, desire to obtain social visibility. Specially, their social representations of drug trafficking influenced the involvement in criminal activities. The main representational elements were “power”, “fame” and “money”, that indicates social representations of drug trafficking were anchored to social representations of hero. Assisted freedom is represented with the following elements: “reflection”, “living together”, “change of behavior”, “professional attendance”, “re-signification of the act”. The internment is represented by “specialized professional attendance”, “living together”, “reflection”, “growth”, “regret”, “learning”, “professional training”, as well as “bad”, “embarrassing”, “ineffective”, “unjust”, “learning of inappropriate behavior”. The analyses of representations of social-educational measures lead to the conclusion that they can be not configured only as prohibitive life experiences, but indeed as social-educational ones. Nonetheless is observed that freedom privation set elements which question the efficacy of internment as a social-educational measure. Social representations of being a woman/a girl reproduce those ones shared by great part of society, which representational elements are: “respect”, “care”, “responsibility” and “honesty”. The representations of being a woman/ a girl found do not endorse criminal activities, which contributes to an elaboration of future prospects that approach to what is social valued. We believe the study findings may assist the implementation of innovative and emancipating public policy, in order to prevent the involvement of girls in criminal activities, and assure human rights throughout the execution of social-educational measures.